2014
DOI: 10.2147/ndt.s71184
|View full text |Cite
|
Sign up to set email alerts
|

Increasing dependency of older people in nursing homes is associated with need for dental treatments

Abstract: To determine relationships between the need for dental treatments of institutionalized elderly people and cognitive impairment and the general level of care needed. Two hundred and sixty-eight residents of long-term care facilities in Germany were included in this study. Age, sex, diseases, number of frequently taken drugs, and location of the long-term care facility of the participants were recorded. For each participant, the need for care was assessed by use of the Barthel index (BI). Cognitive impairment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 35 publications
(56 reference statements)
1
39
0
Order By: Relevance
“…The ROAG is a validated oral problem assessment tool with high sensitivity and specificity . Furthermore, high reproducibility of the ROAG has been reported . In the present study, two experienced dental hygienists carried out the oral assessment using the ROAG on the day of admission.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…The ROAG is a validated oral problem assessment tool with high sensitivity and specificity . Furthermore, high reproducibility of the ROAG has been reported . In the present study, two experienced dental hygienists carried out the oral assessment using the ROAG on the day of admission.…”
Section: Methodsmentioning
confidence: 91%
“…25 Furthermore, high reproducibility of the ROAG has been reported. 21,22,[25][26][27] In the present study, two experienced dental hygienists carried out the oral assessment using the ROAG on the day of admission. The authors translated the ROAG into Japanese with caution to be used only by two experienced dental hygienists, because the ROAG had not been translated into Japanese at the time of this study.…”
Section: Oral Status Assessmentmentioning
confidence: 99%
“…Older people who were dependent on help with self‐care (in one up to all six activities according to Katz's ADL index) had around a sixfold higher risk of oral problems. This result is in line with previous studies that also found increasing dependency to be associated with oral health problems among older people in need of care . Further efforts are needed to ensure that older people with high dependence in daily activities also receive help with oral care as an integrated part of their daily care.…”
Section: Discussionmentioning
confidence: 99%
“…This high level of care dependency, coupled with widespread dementia, can have significant impacts on residents’ oral health status. Recent research has linked increasing care dependency and cognitive impairment with declines in overall oral health and an increased need for dental treatment . Possible explanations for this effect include care providers’ lack of knowledge regarding dental treatment, competing priorities for care staff, lack of cooperation by persons with severe cognitive impairment and inaccessible dental care services …”
Section: Introductionmentioning
confidence: 99%
“…Recent research has linked increasing care dependency and cognitive impairment with declines in overall oral health and an increased need for dental treatment. 18 Possible explanations for this effect include care providers' lack of knowledge regarding dental treatment, competing priorities for care staff, lack of cooperation by persons with severe cognitive impairment and inaccessible dental care services. 19,20 The first step to developing and implementing effective strategies to optimise oral health for long-term care residents is to have a comprehensive understanding of the current state of oral health for residents in Canadian long-term care homes.…”
mentioning
confidence: 99%